Serodiagnosis of Dengue by Particle Agglutination Assay - Sah, OP; Subedi, S; Morita, K; Pandey, BD (Journal of Nepal Health Research Council, 2009)
Background: Dengue is an emerging public health problem in Tarai Region of Nepal. The most affected are among the poorest populations living in remote, rural areas and urban slums who have even no access for medical treatment. This study was carried out with the objective of the determining the serodiagnosis of dengue in symptomatic individuals and comparing it to IgM ELISA. Methods: One hundred eighty three samples were collected from the suspected cases having clinical symptoms of dengue in the Tarai region of Nepal during September to October 2007. Particle Agglutination (PA) assays was performed and it was compared with IgM capture ELISA.  Results: Out of the total of 183 serum samples that 55(30%) samples were positive by PA assay. When compared with IgM-capture ELISA, a 50 of 55 were positive (sensitivity of 98% and specificity of 96%; a positive prediction value of 90% and negative prediction value of 99%). Conclusions: The finding of this study showed that dengue is firmly established in low endemic Tarai region of Nepal. The sensitivity and specificity of PA assay is acceptably high and will be useful in rural areas of Nepal. Key words: Dengue, Tarai region, Particle agglutination test, IgM capture ELISA   DOI: 10.3126/jnhrc.v7i1.2276 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 29-32